ANALISIS FRAMING TERHADAP PEMBERITAAN DIDISKUALIFIKASINYA MIFTAHUL JANNAH DARI CABANG OLAHRAGA JUDO - Buono, Heri; Maulina, Putri; Muzakkir, Muzakkir (Universitas Teuku Umar, 2019)
The disqualification of the blind female athlete of Miftahul Jannah from the Asian Para Games judo in October 2018 was the first time that happened in Indonesia. The purpose of this study was to determine the differences in news frames between AceTrend and Suara.com related to the Miftahul Jannah case by using several concepts of framing elements from Zhongdan Pan and Gerald M. Kosicki in the form of syntax, script, thematic and rhetorical. The concept is based on the theory of Peter L. Berger to dissect a reality of news, namely the Social Construction Theory of Reality. The results show that the AceHTrend frame through its reporting is more prominent on the justifications of attitudes taken by Miftahul Jannah related to its disqualification from the 2018 Asian Para Games judo sports. Meanwhile the news frame of Suara.com in its coverage highlights attitudes that are more inclined to justification regarding rules Refereeing Rules IJF in judo. Suara.com also said in its report that it did not blame the attitude taken by Miftahul Jannah in defending his belief. This shows that Suara.com wants to be neutral while remaining in favor of the rules of Refereeing Rules IJF in judo.Â